The Influence of Practical Lecturer Competence and Innovation on Improving Soft Skills and Hard Skills in Early Children - Gatot Herry Djatmika (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of this study was to determine the relationship and influence between the competence of practical educators and the abilities and knowledge of early childhood in soft skills and hard skills. Problems or difficulties arise when learning does not always run smoothly, including a poor school environment, unattractive learning models and reduced early childhood abilities. This situation is often a problem that often arises in the learning process. Teaching and learning has many objectives to be achieved, including the development and improvement of student performance and skills. The method used is quantitative validation. The target of this study were students from several state early childhood education schools in DKI Jakarta Province with a total of 285 students, and the number of children selected using the purposive sampling method was 165 children. The results of the study show that there is a positive and significant relationship between the competence of practicing teachers and young children (soft skills and hard skills). Practical teacher innovation greatly influences the development of early childhood skills. Meanwhile, the competence and innovation of practicing teachers have a positive and significant effect on improving early childhood skills (soft and hard skills). Based on these findings, schools need to maintain children's achievements and develop children's skills in a sustainable manner by providing experienced and trained teachers